2002
DOI: 10.1007/s00167-002-0330-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight-bearing knee kinematics in subjects with two types of anterior cruciate ligament reconstructions

Abstract: Weight-bearing knee kinematics in patients who received two types of anterior cruciate ligament reconstruction were studied using a fluoroscopy-based three-dimensional measurement technique. Eleven patients with more than 1-year follow-up and good or excellent results participated in this study. Six subjects received anterior cruciate ligament reconstruction using a multiply folded semitendinosus and gracilis tendon graft, and five received combined intra- and extra-articular anterior cruciate ligament reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 33 publications
4
44
0
Order By: Relevance
“…These findings contradict reports from some investigators in which differences between the reconstructed and noninjured legs have been reported for integrated EMG 11,28 and tibial internal/external rotation. 33 However, other investigators have reported results similar to this investigation for integrated EMG, 43 anteriorposterior femoral translation, 22 and tibial internal/external rotation. 22 This controversy makes it unclear if neuromuscular deficits carry over to the noninjured leg in patients with ACL reconstruction or if full recovery of the injured leg can be expected.…”
Section: Drop Jumpsupporting
confidence: 78%
See 2 more Smart Citations
“…These findings contradict reports from some investigators in which differences between the reconstructed and noninjured legs have been reported for integrated EMG 11,28 and tibial internal/external rotation. 33 However, other investigators have reported results similar to this investigation for integrated EMG, 43 anteriorposterior femoral translation, 22 and tibial internal/external rotation. 22 This controversy makes it unclear if neuromuscular deficits carry over to the noninjured leg in patients with ACL reconstruction or if full recovery of the injured leg can be expected.…”
Section: Drop Jumpsupporting
confidence: 78%
“…33 However, other investigators have reported results similar to this investigation for integrated EMG, 43 anteriorposterior femoral translation, 22 and tibial internal/external rotation. 22 This controversy makes it unclear if neuromuscular deficits carry over to the noninjured leg in patients with ACL reconstruction or if full recovery of the injured leg can be expected. On the basis of the results of this investigation, this controversy needs to be analyzed with caution given the range of years after ACL reconstruction of the women who participated in this investigation.…”
Section: Drop Jumpsupporting
confidence: 78%
See 1 more Smart Citation
“…These results are supported by researchers who have shown no differences among graft types used in ACL ligamentoplasty, especially for functional and kinematic outcomes. 1,[35][36][37] Nevertheless, our results cannot be generalized due to the small sample sizes of the 2 subgroups.…”
Section: Joint Kineticsmentioning
confidence: 67%
“…The precisions of the WEMS method are also shown as error bars on the corresponding component curves 3D mandibular kinematics using fluoroscopy have reported SDs of errors as large as 5.6 mm in the out-of-plane translation. 28,29 With the WEMS method for the knee joint, Tsai et al 19 reported precisions of less than 0.77 mm for in-plane translations, less than 1.13 u for all rotations and 3.06 mm for the out-of-plane translation.…”
Section: Figurementioning
confidence: 99%